Transnational Representation in EU National Parliaments: Concept, Case Study, Research Agenda. (May 2020) - Kinski, Lucy; Crum, Ben
This article introduces the notion of 'transnational representation' to refer to claims by national parliamentarians on behalf of citizens of other national constituencies. Thus defined, transnational representation combines insights from the constructivist turn in the theory of democratic representation with a renewed focus on national parliaments as the prime institutional sites of representation. A focus on transnational representation advances the debate on democratic representation in an age of internationalisation in two ways. First, it allows for a systematic and comparative analysis of how representation in parliaments responds to internationalisation. Second, it suggests a new perspective on the possible alignment of political representation with the range of affected interests. We illustrate these two claims with a case study of transnational representation in parliamentary debates on the European Financial Stability Facility and by outlining an agenda for further research.